Thymic hypoplasia in pediatric patients with respiratory illnesses - Fundora-Hernández, Hermes (2023)
Objective: To determine the clinical and epidemiologic features of children with thymic hypoplasia and respiratory illnesses in Cuba. Methods: A retrospective study was conducted among children of 1-6 years of age of both sexes attended at a Pediatric Immunology Program of Hospital Materno Infantil Ángel Arturo Aballí Arellano in Habana, Cuba from September 2019 to August 2022. Children with thymic hypoplasia with and without a history of a respiratory illness either infectious or non-infectious were included.Results: No association between age andsex with thymic hypoplasia but an association was found with children with a severe respiratory illness. Factors associated with a severe respiratory illness were ineffective breastfeeding, history of an atopic condition, pregnancy of high risk, prematurity and exposure to tobacco smoke. Conclusions:Thymic hypoplasia was not associated with age or sex. An association with mild-moderate thymic hypoplasia was found with a severe respiratory illness.